Quality and productivity improvement in a manufacturing company through industrial engineering tools - 433619 Hun, Tiang Song; Mohamed Shariff Nabi Baksh, supervisor; Fakulti Kejuruteraan Mekanikal (Skudai : Universiti Teknologi Malaysia, 2002)
Project Paper (Bachelor of Engineering (Mechanical) - University Teknologi Malaysia, 2002